Proyecto de Inversión para Implementar una Fábrica SEMI-AUTOMÁTICA de ladrillo en el Cantón Catamayo de la Provincia de Loja - Maldonado Cuenca, Jhonatan Adrian (2016)
The present thesis project is called "Project of investment to implement a factory SEMI - automatic of brick in the CANTON CATAMAYO of the province of LOJA". Whose main objective is to encourage the development of Socio-economic, through an investment in a factory project semi-automatic brick in the canton Catamayo of Loja province, which has been met it, with specific objectives. The first objective is to determine the supply and demand in the market, and this became a market study and through the implementation of surveys the current demand for brick, is could learn in terms of the offer it has obtained with the application of interviews with the producers of brick, determining the unmet market demand. The second objective is to establish the technical feasibility for the implementation of the brick factory in the city of Catamayo, so we investigated the productive processes of the brick, both craft and technician, on the other hand is considered machinery appropriate for the development of this activity, additional thereto was made a flow chart that allowed to know in detail the process of brick making. The third objective aims at identifying the fixed costs and variables involved in the process of elaboration of the brick and thus determined the break-even point, in where the company does not win or lose, to manufacture a number of pieces of brick. The fourth objective is to design a manual functions according to structural and organizational of the company operation, it conducted a manual on it detailing the number of staff that the company must take to fulfil its objective, along with the functions that each Member of the company must be, from partners to the workers so that each Member knows its responsibility and not exist double function; emphasizing each of the requirements to take the positions assigned. Finally came to the conclusion of the feasibility, both technical, legal, economic and financial, to implement in the Catamayo Canton factory. So it is recommended to promote the industrial development of the artisan brick factories, and implement technology that benefits both producers and the community in general.